A review on the structural characterization of nanomaterials for nano-QSAR models - Moncho, Salvador; Serrano-Candelas, Eva; de Julián-Ortiz, Jesús Vicente; Gozalbes, Rafael (Beilstein Journal of Nanotechnology, 2024)
Quantitative structure–activity relationship (QSAR) models are routinely used to predict the properties and biological activity of chemicals to direct synthetic advances, perform massive screenings, and even to register new substances according to international regulations. Currently, nanoscale QSAR (nano-QSAR) models, adapting this methodology to predict the intrinsic features of nanomaterials (NMs) and quantitatively assess their risks, are blooming. One of the challenges is the characterization of the NMs. This cannot be done with a simple SMILES representation, as for organic molecules, because their chemical structure is complex, including several layers and many inorganic materials, and their size and geometry are key features. In this review, we survey the literature for existing predictive models for NMs and discuss the variety of calculated and experimental features used to define and describe NMs. In the light of this research, we propose a classification of the descriptors including those that directly describe a component of the nanoform (core, surface, or structure) and also experimental features (related to the nanomaterial’s behavior, preparation, or test conditions) that indirectly reflect its structure.
Keywords: descriptors; nanomaterials; nano-QSAR; QSAR; toxicity